(untitled) (International Journal of Engineering and Computer Science, 2022)
As different types of dynamic networks are developed by easy means of devices, people start using them for various means. Such vulnerable networks are easy places to attack and perform malicious activities. This work develops a model that can generate a path from source to destination in a dynamic node environment without prior information. Path generation artificial immune genetic algorithms will be used, as this algorithms find a good path in a short time. In order to detect the malicious activity, such nodes need to be identified. Hence identification of attackers nodes is done by trust model where Adamic Adar trust function finds the mutual trust value of node as epr past performance of nodes.